Impact of the Alantbahih of subordinates in the promotion of individual creativity: Survey of the views of a sample of employees of the hospitals in Al-Zahrawi and Ibn Sina in the province of Nineveh, educational - سندية مروان سلطان; ميسون عبد الله احمد (Iraqi Journal for Administrative Sciences, 2025)
The Present research study of the impact of operations Alantbahip in the promotion of individual creativity, in the light of analysis of the opinions of subordinates in some of the hospitals in the province of Nineveh, who were randomly selected from hospitals. To this consensus has been promised to design a questionnaire for this purpose, and distributed to the respondents, who numbered (50) person. After analyzing the inter data obtained benefits from the equations of correlation and regression, which was preceded by the provision of a conceptual framework prepared by the researchers, taking advantage of the views of the authors regarding the concepts of individual creativity and operations Alantbahip, concluded researchers at a number of results, which were in the light of crystal matching of the conclusions, perhaps the most important: that the scientific Alantbahip a central role in the promotion of individual creativity is closely influence the subordinates, and so on as he went to the book in theoretical frameworks of organizational behavior since the twenties of the last century, and in light of the conclusions provided researchers their proposals, which emphasize the importance of giving the subject of operations Alantbahip appropriate attention by managers and employees together in ways that enhance individual creativity of subordinates.